1106 Impact of Warmed Inhaled Gas from the Mechanical Ventilator on Esophageal Temperature During Whole Body Hypothermia for Hypoxic-Ischemic Encephalopathy. (October 2012) - Sarkar, S; Sarkar, SS; Bhagat, I; Dechert, R; Donn, SM
Abstract : During whole body cooling (WBC), the core temperature is monitored with either an esophageal or a rectal probe. Most infants are usually on mechanical ventilation while receiving hypothermia. As the temperature in the esophagus responds rapidly to changes in the ambient temperature, inhalation of warmed gas from ventilator during hypothermia may lead to overestimation of ventilated patients' actual temperature, causing automated cooling devices to overcool patients well below set temperature targets. Objective: We determined if the esophageal temperature recordings during therapeutic WBC differ between ventilated and non-ventilated infants. Methods: Twenty-two consecutively cooled infants had simultaneous esophageal and rectal temperatures recorded every 4 hours during 72 hours of WBC. The later was deemed to be actual core temperature. Other clinical monitoring and treatment during hypothermia were as per established protocol. Results: Fourteen infants received mechanical ventilation throughout cooling. The remaining 8 infants were on ventilator initially but got extubated and were not on ventilator during 32 to 72 hours section of WBC. Esophageal temperatures were significantly higher than simultaneous rectal temperatures (p≤0.01 at each time point) for all 22 infants. However, the esophageal temperatures across every 4 hour time points during 32 to 72 hours section of WBC did not differ between the ventilated (n-14), and non-ventilated (n-8) infants. The magnitude (median, IQR) of the difference between esophageal and rectal temperatures were also similar between the 2 groups. Conclusions: Warmed inhaled gas does not interfere with the esophageal temperature during WBC.